Other Orientation dan Self Interest dalam Memotivasi Perilaku Kewarganegaraan Organisasi - Dony - Hendartho (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
In a public organization, each employee is expected to play a role according to job descriptions, superior decisions, and applicable regulations. However, sometimes employees behave voluntarily to do work outside the call of duty. This action is called Organizational Citizenship Behavior (OCB). The purpose of this paper is to define OCB and explain how to improve performance and well-being of organization. The effect of self interest and other orientation in motivating OCB in an organization will also be presented. The motivational strength of employees varies in terms of self-interest and other orientation. People who have a high other orientation tend to be involved in OCB; but people who have high self-interest are also willing to participate in OCB. This paper shows that OCB plays a very important role in the continuity and success of public services.